Beyond Normative Control: Against the Will Theory of Rights. Issue 4 (23rd May 2020) - Bowen, Joseph
Abstract: The Will Theory of Rights says that having control over another's duties grounds rights. The Will Theory has commonly been objected to on the grounds that it undergenerates right-ascriptions along three fronts. This paper systematically examines a range of positions open to the Will Theory in response to these counterexamples, while being faithful to the Will Theory's focus on normative control. It argues that of the seemingly plausible ways the defender of the Will Theory can proceed, one cannot both be faithful to the theory's focus on normative control as the grounds of rights and achieve extensional adequacy.